Febuxostat-induced agranulocytosis in a pediatric hematopoietic stem cell transplant recipient: Case Report and literature review - Curci, Debora; Braidotti, Stefania; Maximova, Natalia (Frontiers in Pharmacology, 2024)
This report describes a pediatric case of isolated agranulocytosis occurring months after hematopoietic stem cell transplantation (HSCT). Secondary cytopenia, or secondary transplant failure, affects 10%-25% of HSCT recipients, with potential triggers including viral infection, graft-versus-host disease (GVHD), sepsis, and certain medications. Viral reactivation was ruled out based on negative PCR results, while GVHD and sepsis were ruled out based on the patient's clinical presentation. The patient, who received an HLA 10/10 unrelated donor T-cell transplant, underwent standard myeloablative conditioning to minimize the risk of graft rejection. However, agranulocytosis persisted even after discontinuation of myelotoxic drugs such as valganciclovir and ruxolitinib. Further investigation revealed that the patient had been taking febuxostat, which was subsequently discontinued, leading to a recovery of the neutrophil count. The European Medicines Agency lists agranulocytosis as a rare side effect of febuxostat. The effect of candidate genes and variants involved in febuxostat pharmacokinetics and pharmacodynamics was done using the Pharmacogenomics Knowledge Base (PharmGKB) to accurately evaluate an individual's risk for neutropenia. This case suggests that genetic variants in renal transporters ABCG2 (exonic non-synonymous variant, rs2231137), SLC29A1 (rs747199 and rs628031), and ABCC4 (3' UTR SNP, rs3742106 and rs11568658) may contribute to drug-induced agranulocytosis. This finding underscores the importance of genetic profiling in the management of patients undergoing HSCT to prevent adverse drug reactions.